Methods for recognition and avoiding social engineering attacks - Olenich, D. (ТДАТУ, 2018)
EN: The article is devoted to the psychological manipulation technique, which is often used in order to induce a person to perform certain actions or to disclose confidential information, and to the methods of protection against it. UK: Статтю присвячено психологічній маніпулятивній техніці, яку часто використовують з метою спонукати людину виконати певні дії чи розголосити конфіденційну інформацію, та основним методам захисту від неї.
Keywords: маніпулятивна техніка; manipulation technique; social engineering; cybercriminals